1)x6-1;x6+1 2)x6-y6;x12-y4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2: \(=\dfrac{\left(x-y\right)\left(x+y\right)\left(x^2+y^2\right)}{-\left(x-y\right)\left(x^2+xy+y^2\right)}=\dfrac{-\left(x+y\right)\left(x^2+y^2\right)}{x^2+xy+y^2}\)
lim x → − ∞ x 6 + 2 3 x 3 − 1 = lim x → − ∞ x 6 1 + 2 x 6 x 3 3 − 1 x 3 = lim x → − ∞ − x 3 1 + 2 x 3 x 3 3 − 1 x 3 = lim x → − ∞ − 1 + 2 x 3 3 − 1 x 3 = − 1 3
Chọn đáp án A
\(a,Sửa:25x^2-20xy+4y^2=\left(5x-2y\right)^2\\ b,=\dfrac{1}{4}\left(\dfrac{1}{9}a^2-b^2\right)=\dfrac{1}{4}\left(\dfrac{1}{3}a-b\right)\left(\dfrac{1}{3}a+b\right)\\ c,=\dfrac{1}{8}\left(a+2\right)^3-1=\left[\dfrac{1}{2}\left(a+2\right)\right]^3-1=\left[\dfrac{1}{2}a+1\right]^3-1\\ =\left(\dfrac{1}{2}a+1-1\right)\left(\dfrac{1}{4}a^2+a+1+\dfrac{1}{2}a+1+1\right)\\ =\dfrac{1}{2}a\left(\dfrac{1}{4}a^2+\dfrac{3}{2}a+3\right)\\ d,=\left(x^3-1\right)\left(x^3+1\right)\\ =\left(x-1\right)\left(x+1\right)\left(x^2-x+1\right)\left(x^2+x+1\right)\)
( 1 + 9 - 9 ) x 6 + 3 : 2
= ( 10 - 9 ) x 6 + 1,5
= 1 x 6 + 1,5
= 6 + 1,5
= 7,5
# Học tốt ! #
câu hỏi là j v bn